Tracking in Nature's Footsteps: The Intersection of Environmental Education and Philosophy - Dakkal Harahap; Tobroni , Tobroni; Widodo, Joko (CV. Bimbingan Belajar Assyfa, 2023)
The ecological crisis has hit parts of the world due to the imbalance in the relationship between humans and nature, so it is very important and urgent to have a practical and scientific understanding of environmental education with ethical and conceptual reflections from philosophy. This research aims to answer the research question,